Archeologie identitaire et construction politique chez Kogălniceanu et Bălcescu - Marton, Silvia (2005)
Abstract: Mihail Kogălniceanu and Nicolae Bălcescu, historians, writers and politicians, important actors of the revolution of 1848 in the Romanian Principalities, dedicated much of their early historical writings to the justification of the nationstate. Their main concern, common to the ’48 generation across Europe, was to answer to the most important question related to the process of nation building and state building: ”Who are we?”, 1848 being for the Romanians the first moment of the collective constitutional memory. The article contends that the two historians retroactively applied to the past categories specific to the 19th century, the past itself being a weapon and guide for the future. Both Kogălniceanu and Bălcescu submitted the political project of nation-state building to a archeology identity called upon to justify